Bullous varicella in a preschool-aged patient - Pavlyshyn, Halyna; Horishna, Ivanna (Pediatria Polska - Polish Journal of Paediatrics, 2019)
Varicella (chickenpox) is a highly contagious febrile rash illness caused by primary infection with Varicella zoster virus (VZV/HHV-3), which is one of the eight human herpes viruses, transmitted by respiratory contact with aerosolised respiratory secretions and blister secretions or by direct contact with them. The typical course of varicella in immunocompetent unvaccinated children is generally mild and uncomplicated. A clinical case of atypical bullous varicella in a preschool child, who was thought to be immunocompetent, was consequently analysed. The disease had typical moderate course, aggravated with characteristic skin syndrome. Hospitalisation and adequate, timely treatment of the patient according to modern guidelines led to his fast, complete recovery and showed the effectiveness of such therapy.